Development of Audio-Visual Teaching Materials in Learning Maharat Al-Kalam Subject - Yusuf, Muhammad; Marwati, Marwati; Asriyah, Asriyah (Attractive : Innovative Education Journal, 2022)
Learning Arabic is closely related to information and communication technology literacy. Specifically, learning maharat al-kalam (speaking skill) has strong relevance to the use of audio-visual media. This article studies the development of audio-visual teaching language in learning it for second-semester students of the Arabic Language and Literature Department, Faculty of Adab and Humanities, UIN Alauddin Makassar in 2022. The data collection lasted for six months through observations, interviews, and documentation guided by instruments in the form of guidelines for each technique. Sometimes one type of data is searched using the three techniques at once, and sometimes it is done separately. The collected data is then classified, systematized, and analyzed based on theoretical guidance. The development of teaching materials using audio-visual in learning it faces various obstacles and problems. IT literacy is still low for lecturers, so it is necessary to improve multimedia and lecturers' IT competence and literacy to support the use of audio-visual media practiced by native speakers in developing teaching materials for the maharat al-kalam subject. The others consist of the lack of mufradat, the lack of student knowledge about sentence patterns, input (students) from high school and vocational school do not have basic knowledge of Arabic, and the lack or unfavorable support for the Arabic language environment. Keywords: Learning Maharat Al-Kalam, Teaching Materials, Development of Audio-Visual